Business Planning and Organizational Profitability: A Study of PPMC Approach - Rabson Iniobong Cletus; Akwari Wisdom; Rufus Emmanuel-Ubong Ita; Bassey Gift Eja; Haruna Adamu Sezuo; Christiana Joseph Ogar (Law and Economy, 2024)
The purpose of the study was to examine business planning and organizational profitability. A study of selected organizations in Cross River State, Nigeria. The objectives were to determine the relationship between marketing plan and company turnover rate, to determine the relationship between financial plan and company market share and to determine the relationship between personal plan and quality of product. Desk survey method was used in gathering relevant information on Business corporate planning and organizational profitability. The study adopted Pearson Product Moment Correlation Statistical tool to examine the relationship between independent and dependent variables. Based on the analysis, the findings revealed that marketing plan had a significant relationship with company turnover rate, financial plan had a significant relationship with company market share and personal plan had a significant relationship with quality of product. The study recommended that policies should be disseminated down the line of management. There is an urgent need for all corporate management units to develop a policy that will be non-ambiguous, set out clear targets with well-defined objectives.